GAMBARAN UMUM PERILAKU KETERGANTUNGAN INSTAGRAM TERHADAP SISWA TINGKAT X SMK NEGERI 2 CIMAHI - lite nurulail aladawiah30; Rosita, Tita; Irmayanti, Rima (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The aim of this research is to find out the profile or general picture regarding the use of Instagram which is currently popular among teenage students, as well as reducing the level of dependence experienced by teenage students. In this study, the approach used is quantitative with descriptive methods. Sampling was used by random sampling with a total sample of 106 students from one class X Mechatronics department at SMK Negeri 2 Cimahi. The aim of this research is to determine the profile of Instagram dependence among students. There are aspects that are the basis for knowing Instagram dependence, including 4 aspects, namely, Tolerance, Mood Modification, Replase, Conflict. Data collection techniques by conducting an instrument distribution in the form of a questionnaire to students who are the research sample. The research results show that students with Instagram dependence in class X mechatronics are in the High category 15%, Low category 16%, and in the Medium category 69%. After knowing the level of dependence on Instagram among students, the next step is to design programs and provide services based on the results of this research. In providing services, students are directed to carry out interviews to find out whether the services provided are acceptable to students and whether students experience a decrease in their use of Instagram. The next step is to give the posttest to students again so that a comparison can be carried out, so that it can be seen that H0 is rejected and H1 is accepted so that it can be concluded that the group guidance service is declared effective